Imaging transient ischaemic attack with diffusion weighted magnetic resonance imaging. (30th April 2010) - Wallis, Adam; Saunders, Tim
Abstract : Transient ischaemic attack can be difficult to diagnose clinically. This article guides you through the radiological options available and highlights the role of diffusion weighted magnetic resonance imaging in detecting acute ischaemia